Un sublime minore. Nel segno di "Marcel Proust e i segni" - Vignola, Paolo (Scenari, 2024)
The paper aims to trace a common thread within the various Deleuzian readings of Kant and Deleuze’s original proposal regarding the transcendental genesis of thought, with particular reference to the concept of the sublime, the problematic nature of such readings and the process of variation that Deleuze imprints on them. In addition to the Deleuzian essays on Kant, the heart of the text is Marcel Proust and the Signs, presented here both as a conceptual counterpoint to The Critical Philosophy of Kant, and as a strategic text with respect to Deleuze’s entire philosophical work. In this confrontation between the interpretative analyses of temporality and the sublime in Kant and the aesthetic and theoretical proposal generated from Marcel Proust and the Signs, the problematic nature of the concept of the sublime emerges, which is dealt with by having recourse to a heterogeneous set of texts from the secondary bibliography, of which an attempt is made to recognize a functional track that is closer to the conceptual transformation work carried out by Deleuze in relation to Kant. This recognition leads thus to present the hypothesis that a sort of “minor sublime” takes shape in Deleuze, as the result not of a radicalisation of the Kantian transcendental and the Analytics of the Sublime, but rather of a more heterodox and heterogenetic operation, which in the text is conceived as “machinic” and subtractive, where only the subtraction of the unity of the soul and the logical use of the faculties allows us to think of the genesis of experience in the terms proposed by Deleuzian elaboration.